Review of the dissertation by S. I. Cherepanov “Comparative-legal study of the jury institution in the Russian Empire according to the 1864 judicial reform and the advocacy institution in the Russian Federation” (Nizhniy Novgorod, 2018. 192 p.) - V. M. Bolshakova (Russian Journal of Economics and Law, 2019)
Objective: to comprehensively and objectively assess the dissertation by S. I. Cherepanov “Comparative-legal study of the jury institution in the Russian Empire according to the 1864 judicial reform and the advocacy institution in the Russian Federation”, defended in Nizhny Novgorod Academy of the Russian Ministry of Internal Affairs in 2019.Methods: method of complex analysis of scientific text, methodology of chrono-discrete monogeographical comparative legal research.Results: the paper presents the author’s conception of chrono-discrete development of the advocacy in Russia, focusing on the theoretical merits of the work and the author’s practical recommendations for improving the advocacy institution in the Russian Federation. In the first chapter, the author examines advocacy as chrono-discrete Russian institution, explores the normative base of the advocacy functioning in the Russian Empire and the Russian Federation, as well as the periodization of the advocacy history in Russia. The second chapter is devoted to the analysis of the legal status and corporate structure of the jury and advocacy in the Russian Empire and the Russian Federation, as well as the advocacy functions in the pre-revolutionary and modern periods. At the same time, there are some criticisms of the applicant’s work. In general, it is concluded that the reviewed work is written at a high level, meets all the requirements for PhD theses, and its author deserves the PhD (Law) degree. Scientific novelty: for the first time, a comprehensive assessment is given to S. I. Cherepanov’s dissertation “Comparative- legal study of the jury institution in the Russian Empire according to the 1864 judicial reform and the advocacy institution in the Russian Federation”.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and legislative activities in the consideration and study of issues related to the advocacy.